Chemical cross‐linking and mass spectrometry to determine the subunit interaction network in a recombinant human SAGA HAT subcomplex. (14th April 2015) - Nguyen‐Huynh, Nha‐Thi; Sharov, Grigory; Potel, Clément; Fichter, Pélagie; Trowitzsch, Simon; Berger, Imre; Lamour, Valérie; Schultz, Patrick; Potier, Noëlle; Leize‐Wagner, Emmanuelle
Abstract Understanding the way how proteins interact with each other to form transient or stable protein complexes is a key aspect in structural biology. In this study, we combined chemical cross‐linking with mass spectrometry to determine the binding stoichiometry and map the protein–protein interaction network of a human SAGA HAT subcomplex. MALDI‐MS equipped with high mass detection was used to follow the cross‐linking reaction using bis[sulfosuccinimidyl] suberate (BS3) and confirm the heterotetrameric stoichiometry of the specific stabilized subcomplex. Cross‐linking with isotopically labeled BS3 d0‐d4 followed by trypsin digestion allowed the identification of intra‐ and intercross‐linked peptides using two dedicated search engines: pLink and xQuest. The identified interlinked peptides suggest a strong network of interaction between GCN5, ADA2B and ADA3 subunits; SGF29 is interacting with GCN5 and ADA3 but not with ADA2B. These restraint data were combined to molecular modeling and a low‐resolution interacting model for the human SAGA HAT subcomplex could be proposed, illustrating the potential of an integrative strategy using cross‐linking and mass spectrometry for addressing the structural architecture of multiprotein complexes.